Development of sputtered BiVO4-CuO Tandem cells for bias-free solar water splitting - Rabelo, Lucas Gabriel (2023)
Photoelectrochemical (PEC) water splitting has been considered as a promising technique for converting abundant solar energy into clean and renewable hydrogen (H2) fuel. Recently, Tandem PEC cells based on stable and low-cost metal oxides have attracted tremendous attention for cleaving water molecules into green H2 assisted only by solar energy. In this work, BiVO4/FeNiOx photoanodes and CuO photocathodes were synthesized via magnetron sputtering deposition to perform oxygen and hydrogen evolution reactions (OER and HER), respectively, in a simple and low-cost Tandem PEC cell. In particular, the all-sputtered BiVO4/FeNiOx photoanode showed excellent PEC performance and chemical stability for OER, achieving a high photocurrent density of +1.22 mA cm-2 and a charge transfer efficiency of 96 % at the water oxidation potential. In contrast, the all-sputtered CuO photocathode exhibited a modest PEC performance for HER, with an onset potential at 1.03 V vs. RHE (reversible hydrogen electrode) and photocurrent density of 0.35 mA cm-2 at +0.40 V vs. RHE. In this work, we also introduced a feasible model based on classical band theory to evaluate the interfacial band alignment of photoelectrodes under working conditions for PEC water splitting. Our energy band diagrams under simulated illumination demonstrated that the photogenerated holes (electrons) at the BiVO4/FeNiOx (CuO) film have enough energy to perform the OER (HER) without external bias. Encouragingly, our novel BiVO4/FeNiOx - CuO Tandem PEC device produced a stable operating photocurrent density of ~50 µA cm-2 under zero-bias and AM 1.5G illumination for at least 1000 seconds, evidencing the occurrence of bias-free solar water splitting reactions. Nevertheless, our proposed Tandem system is still far from meeting the requirements for practical applications due to the severe chemical instability and low photocurrent density of the CuO film. Therefore, further studies must be directed towards producing protective layers, inducing p-n heterojunction, and depositing HER cocatalysts for enhancing the chemical stability and PEC performance of the CuO film. In summary, we aimed herein to propose a scalable methodology for developing metal oxidebased Tandem PEC cells and to introduce suitable tools for assessing interfacial band alignment of photoelectrodes under working conditions for PEC water splitting. This work also thoroughly discusses the fundamental limitations, current challenges, and prospects for employing Tandem PEC devices to produce green hydrogen as a clean and renewable energy carrier.